The mechanism of impaired delayed recall verbal memory function in Parkinson's disease with orthostatic hypotension: a multiple imaging study - Xue, Xiaofan; Huang, Anqi; Zeng, Jingrong; Song, Haixia; Xing, Yingqi; Chan, Piu; Xu, Erhe; Zhou, Lichun (Frontiers in Neurology, 2023)
Introduction Orthostatic hypotension (OH) frequently accompanies autonomic dysfunction and is an important risk factor for cognitive impairment in Parkinson's disease (PD). However, the association between different cognitive functions and OH in PD patients is not yet fully understood. Methods This study aimed to evaluate the scores of different cognitive domains and multiple parameters using different imaging techniques on PD patients with or without OH. A total number of 31 PD patients with OH (n = 20) and without OH (n = 11) were recruited from the Department of Neurology, Beijing Xuanwu Hospital for this study. All patients underwent beat-to-beat non-invasive blood pressure recordings and an active standing test to evaluate neurogenic OH and a global neuropsychological test to assess cognitive function. All patients underwent dynamic cerebral autoregulation (dCA) measurement, brain magnetic resonance imaging (MRI), and brain 18fluorine-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT). Results The results showed that OH patients had poor delayed recall verbal memory when compared with the PD patients without OH (1.75 ± 1.59 vs. 3.10 ± 1.73, p = 0.042). The dCA test indicated a significant difference in the right very low-frequency (VLF) gain between two groups (1.27 ± 0.17 vs. 1.10 ± 0.26, p = 0.045) and the brain 18F-FDG PET/CT indicated a significant difference in the SUV (right medial temporal lobe) to SUV (occipital lobe) ratio (0.60 ± 0.08 vs. 0.67 ± 0.11, p = 0.049). Meanwhile, these two imaging parameters were negatively correlated (p < 0.001). Furthermore, the score of a delayed recall verbal memory in the OH group was positively correlated with the right medial temporal lobe to occipital lobe ratio (p < 0.001) and was negatively correlated with the right VLF gain (p = 0.023). Discussion PD with OH patients had poor delayed recall memory, which might have been caused by the decreased metabolic dysfunction of specific medial temporal lobe due to the impaired dCA ability.